Анализ, проектирование и реализация ТРКМ учащихся в процессе обучения русскому языку - Вегнерис, О.Г. (My University, 2016)
Relevance. Technjlogy. The Quality of education Using Monitoring.
Keywords: technology development of critical thinking; lesson,pupit; development; SWOT-analysis